2021
DOI: 10.1101/2021.03.01.21252330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Telemedicine Reduce health disparities? Longitudinal Evidence during the COVID-19 Pandemic in the US

Abstract: Objective: The COVID-19 pandemic could be a significant health issue for the elderly population and those with pre-excising chronic condition. In response to the pandemic health care services have increased the use of telehealth medicine. The propose of this study is to examine factors associated with access to telemedicine before and after COVID-19 based on sociodemographic factors and type of chronic disease. Method: We have used data from the Research and Development Survey (RANDS) at two different time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In our logistic regression analysis, we found that people with no education and less than 10 years of education were significantly more WRTCCD compared to the people with more than 10 years of education. Similar findings were found in the United States, where those with lower levels of education accessed telemedicine at a higher rate as the pandemic progressed [ 17 ]. This trend might be due to patients with a higher level of education being more concerned about the privacy issues involved with telemedicine.…”
Section: Discussionsupporting
confidence: 79%
“…In our logistic regression analysis, we found that people with no education and less than 10 years of education were significantly more WRTCCD compared to the people with more than 10 years of education. Similar findings were found in the United States, where those with lower levels of education accessed telemedicine at a higher rate as the pandemic progressed [ 17 ]. This trend might be due to patients with a higher level of education being more concerned about the privacy issues involved with telemedicine.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, it is intuitive to introduce a telemedicine curriculum in medical schools and propose a model of education to effectively leverage telemedicine technologies and artificial intelligence in patient management [ 57 , 58 ]. Mainstreaming telemedicine and video applications in health systems could reduce health care disparities [ 59 ]. The surge in developing telemedicine applications with video call features is one of the most defining trends in this decade and will have a profound impact on socioeconomic and geopolitical realities, in particular in low- and middle-income countries (LMIC) [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inequality of socioecomic status may exacerbate health care disparities. The disparities also exist in many clinical fields [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , departments, and countries, but no evidence shows the disparity in the oncology department currently. In this study, we demonstrated patient's forms of care adoption is associated with socioeconomic characteristics during the transition.…”
Section: Introductionmentioning
confidence: 99%